Across-rotation genetic analysis and multitrait selection in a cloned cross of Eucalyptus urophylla × E. tereticornis - Xu, Jiahong; Zhou, Mingming; Weng, Qijie; Li, Mei; Gan, Siming (Frontiers in Plant Science, 2025)
Clonal testing is crucial for estimating genetic parameters and selecting elite clones. However, few studies have tested clones over two or more rotations. In this study, a clonal trial of the sibs from a Eucalyptus urophylla × Eucalyptus tereticornis cross was used for genetic parameter analyses and multitrait selection based on traits such as across-rotation growth, wood properties, coppicing ability, and coppice chlorophyll fluorescence. Clonal repeatability (H2) estimates for growth traits in the first rotation ranged from 0.73 (diameter at breast height at age 15) to 0.84 (single-tree volume at age 2.5) and were generally higher than those for growth traits in the second rotation (0.11–0.62). H2 estimates for coppicing and chlorophyll fluorescence traits ranged from 0.35 to 0.57 and 0.03 to 0.53, respectively, indicating low to medium genetic control of these traits. Phenotypic correlations (rp) and additive genetic correlations (rg) were generally high among growth traits within a single rotation and among coppicing traits but varied considerably across other trait pairs. In particular, second-rotation volume at 2.5 years showed a very weak rp but a moderately positive rg with early-stage volumes from the first rotation. Multitrait selection index (SI) and multitrait genotype–idiotype distance index (MGIDI) methods were applied at a selection intensity of 15% under four scenarios, each combining two to five traits. Relative genetic gain (RG) and selection efficiency (E) estimates were positive for all traits included in multitrait selection, indicating the usefulness of all selection scenarios. Compared to SI, the MGIDI method produced slightly lower RG and E values for volumes at ages 8 and 15 years, but higher RG and E values for wood basic density and cellulose content at age 8 in the first rotation. This study has important implications for eucalypt clonal breeding and management.